PROTOTIPE SISTEM JEMURAN OTOMATIS BERBASIS IOT (INTERNET OF THINGS) MENGGUNAKAN METODE FUZZY TSUKAMOTO - Agus Setiawan; Mukti Qamal; Rini Meyanti (LPPM Universitas Abdurrab, 2026)
The development of Internet of Things (IoT) technology has provided practical solutions for various aspects of daily life, including smart home applications. One household activity that remains largely manual is clothes drying, which is highly dependent on unpredictable weather conditions. This study aims to develop an IoT-based automatic clothesline system using the Fuzzy Tsukamoto method to respond automatically to changing environmental conditions. The system employs a rain sensor, light sensor (LDR), and DHT22 temperature and humidity sensor to monitor environmental conditions in real time. Sensor data are processed using the Fuzzy Tsukamoto method to determine whether the clothesline should be opened or closed and to control a blower fan inside the drying chamber. The system is also integrated with a mobile application for remote monitoring and control. The test results show that all implemented functions achieved a 100% success rate, with a system response time of 0–5 seconds to changes in sensor conditions. These results demonstrate that the proposed system operates automatically and responsively, improving the efficiency and convenience of clothes drying under changing weather conditions.